Evaluasi Kualitas Informasi Perusahaan Tercatat di Bursa Efek Indonesia Periode 2018-2019 - Wing Wahyu Winarno (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2021)
One of the main sources of information about go public firms is from the official website of the capital market. In Indonesia, it is www.idx.co.id. Public firms have obligation to submit annual report and other corporate actions through this website. If all firms fulfill their obligation to submit annual report, the number of listed firms should be equal to the number of the annual reports submitted. Unfortunately, this is not the case. This study will evaluate the concistency of the information in IDX website, by comparing the number of listed companies and the annual reports that were submitted by those firms. The period used is two years, covering 2018 and 2019 period. Results reveal that according to the website, there are 737 listed firms, but this research shows that the number of listed firms in 2018 and 2019 are 785 and 792, respectively. There are also some inconcistencies between the number of annual reports submitted, which are 48 annual reports (2018) dan 55 annual reports (2019) that were submitted by firms that were not listed in the web for the respective year. Another inconcistency it that there are 47 and 20 firms for the year 2018 and 2019, respectively, that did not submit the annual reports. The contribution of this study is to evaluate the consistency of the information presented on the www.idx.co.id page and not many researchers havedone the same.